Gameconomics from Policy Dynamics Analysis Perspective (Study Case: Esports Policy in Indonesia) - Putu Radar Bahurekso; Sinta Ningrum; Mas Dadang Enjat Munajat (Dinasti International Journal of Education Management And Social Science, 2025)
This study analyses the policy dynamics of esports in Indonesia and its economic potential within the context of the digital economy. Using a qualitative descriptive approach, the research explores the transformation of esports policies from unrecognised to becoming a professional sports branch, including the impact of revising Law No. 3 of 2005 into Law No. 11 of 2022. The findings indicate that esports has significant economic potential, with Indonesia's gaming industry's revenue reaching USD 1.1 billion in 2023. However, challenges such as the lack of comprehensive regulations, the dominance of foreign companies, and infrastructure limitations still need to be addressed. This study recommends inclusive policies to support local developers, strengthen the ecosystem, and utilize esports as a key driver of Indonesia's digital economy.